Review and Bibliometric Analysis of Biogas Power Plants in Indonesia - Dhasa Ikrar Setyanansyach; Muji Setiyo; Thirunavukkarasu Raja (Universitas PGRI Semarang, 2023)
The demand for energy is increasing due to population growth, technological advancements, and a growing need for sustainable energy sources. Indonesia, which faces an energy deficit, is exploring alternatives to fossil fuels. Biogas, produced through the anaerobic fermentation of organic matter, offers a clean and sustainable energy option while addressing waste disposal issues. Therefore, this literature review examines various aspects of a biogas power plant, including a feasibility study that encompasses technical and economic analyses, generator design, trials, implementation, and post-implementation evaluation. In this review, we gathered scientific papers from Google Scholar using the keywords